How Does Blood-Retinal Barrier Breakdown Relate to Death and Disability in Pediatric Cerebral Malaria?. (26th August 2020) - MacCormick, Ian J C; Barrera, Valentina; Beare, Nicholas A V; Czanner, Gabriela; Potchen, Michael; Kampondeni, Samuel; Heyderman, Robert S; Craig, Alister G; Molyneux, Malcolm E; Mallewa, Macpherson; White, Valerie A; Milner, Dan; et al.
Abstract: Background: In cerebral malaria, the retina can be used to understand disease pathogenesis. The mechanisms linking sequestration, brain swelling, and death remain poorly understood. We hypothesized that retinal vascular leakage would be associated with brain swelling. Methods: We used retinal angiography to study blood-retinal barrier integrity. We analyzed retinal leakage, histopathology, brain magnatic resonance imaging (MRI), and associations with death and neurological disability in prospective cohorts of Malawian children with cerebral malaria. Results: Three types of retinal leakage were seen: large focal leak (LFL), punctate leak (PL), and vessel leak. The LFL and PL were associated with death (odds ratio [OR] = 13.20, 95% confidence interval [CI] = 5.21–33.78 and OR = 8.58, 95% CI = 2.56–29.08, respectively) and brain swelling ( P  < .05). Vessel leak and macular nonperfusion were associated with neurological disability (OR = 3.71, 95% CI = 1.26–11.02 and OR = 9.06, 95% CI = 1.79–45.90). Large focal leak was observed as an evolving retinal hemorrhage. A core of fibrinogen and monocytes was found in 39 (93%) white-centered hemorrhages. Conclusions: Blood-retina barrier breakdown occurs in 3 patterns in cerebral malaria. Associations between LFL, brain swelling, and death suggest that the rapid accumulation of cerebral hemorrhages, with accompanying fluid egress, may cause fatal brain swelling. Vessel leak, from barrier dysfunction, and nonperfusion were not associated with severe brain swelling but with neurological deficits, suggesting hypoxic injury in survivors. Abstract : Fluorescein angiography provides evidence that in cerebral malaria severe brain swelling and death are due to fluid egress from multiple small cerebral hemorrhages. In contrast, neurological deficits in survivors are associated with vessel leak and capillary nonperfusion.